Magnetic correlations in infinite-layer nickelates: An experimental and theoretical multimethod study - Ortiz, R. A.; Puphal, P.; Klett, M.; Hotz, F.; Kremer, R. K.; Trepka, H.; Hemmida, M.; Von Nidda, H-A Krug; Isobe, M.; Khasanov, R.; Luetkens, H.; Hansmann, Philipp; et al. (Physical Review Research, 2022)
We report a comprehensive study of magnetic correlations in LaNiO2, a parent compound of the recently discovered family of infinite-layer (IL) nickelate superconductors, using multiple experimental and theoretical methods. Our specific heat, muon-spin rotation (µSR), and magnetic susceptibility measurements on polycrystalline LaNiO2 show that long-range magnetic order remains absent down to 2 K. Nevertheless, we detect residual entropy in the low-temperature specific heat, which is compatible with a model fit that includes paramagnon excitations. The µSR and low-field static and dynamic magnetic susceptibility measurements indicate the presence of short-range magnetic correlations and glassy spin dynamics, which we attribute to local oxygen nonstoichiometry in the average infinite-layer crystal structure. This glassy behavior can be suppressed in strong external fields, allowing us to extract the intrinsic paramagnetic susceptibility. Remarkably, we find that the intrinsic susceptibility shows non-Curie-Weiss behavior at high temperatures, in analogy to doped cuprates that possess robust nonlocal spin fluctuations. The distinct temperature dependence of the intrinsic susceptibility of LaNiO2 can be theoretically understood by a multimethod study of the single-band Hubbard model in which we apply complementary cutting-edge quantum many-body techniques (dynamical mean-field theory, cellular dynamical mean-field theory, and the dynamical vertex approximation) to investigate the influence of both short- and long-ranged correlations. Our results suggest a profound analogy between the magnetic correlations in parent (undoped) IL nickelates and doped cuprates.
CRIS-Team Scopus Importer:2022-06-10